2005
DOI: 10.1249/01.mss.0000179096.03129.a4
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation Reduces Muscle Inosine Monophosphate during Endurance Exercise in Humans

Abstract: Raising muscle total Cr content before exercise appears to improve the ability of the muscle to maintain energy balance during intense aerobic exercise, but not during more moderate exercise intensities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…Due to the intensity and time duration (two minutes) of the interval work periods, it was hypothesized that Cr would provide for a greater training capacity, and, therefore, the Cr group would show greater improvements in the testing measurements. McConell and colleagues [45] found that Cr improved the maintenance of energy balance in the muscle during intense aerobic exercise; however, performance was not improved, which is in agreement with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the intensity and time duration (two minutes) of the interval work periods, it was hypothesized that Cr would provide for a greater training capacity, and, therefore, the Cr group would show greater improvements in the testing measurements. McConell and colleagues [45] found that Cr improved the maintenance of energy balance in the muscle during intense aerobic exercise; however, performance was not improved, which is in agreement with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Creatine is the biochemical precursor of high energetic phosphocreatine and its higher storage may be associated with the applied diet. On the other hand, its higher level at the supplementation was found to be in negative correlation with IMP (known as the indicator of hypoxemia condition) during endurance exercise in humans [39, 40]. An increased level of methylhistidine in tissues may be a sign of muscle protein breakdown [41], while increased levels of tissue methionine may be a defense response against cell fat deposition [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus TCr (mM) and mitochondrial protein (mg) were added to the respiration chamber at ratios below and above the ratios of capacitance to resistance in intact muscle. Specifically, mixed human skeletal muscle contains ϳ30 mol TCr/g muscle (41,58) and 10 mg mitochondrial protein per gram wet muscle (49), giving a ratio of ϳ3.0 (mol TCr/mg mitochondrial protein). Because we routinely incubate ϳ0.1 mg mitochondrial protein in our assays, a range of TCr above and below 0.3 mol was employed.…”
Section: Discussionmentioning
confidence: 99%